2018
DOI: 10.2174/1389200219666180101104159
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus - Pharmacokinetic Considerations for Clinicians

Abstract: These findings are interesting and relevant to transplant physicians and physicians interested in immunosuppressive therapy. We therefore review current state of the art aspects of tacrolimus pharmacokinetics including genetics or different tacrolimus formulations (twice-daily immediate-release tacrolimus capsules, once-daily extended- release tacrolimus capsules; novel once-daily tacrolimus tablets) and their possible clinical impact including practical considerations for clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 0 publications
1
75
2
2
Order By: Relevance
“…2 Second, in contrast to European studies, Bartlett et al's study included 40% African Americans; ethnicity has a known impact. 6,7 Third, the low rejection rate (e.g., in contrast to Egeland et al), might have masked differences as already stated by the authors. Different induction therapies and missing protocol biopsies, frequently detecting rejection in stable grafts, might be responsible.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…2 Second, in contrast to European studies, Bartlett et al's study included 40% African Americans; ethnicity has a known impact. 6,7 Third, the low rejection rate (e.g., in contrast to Egeland et al), might have masked differences as already stated by the authors. Different induction therapies and missing protocol biopsies, frequently detecting rejection in stable grafts, might be responsible.…”
mentioning
confidence: 78%
“…2,4 Lower troughs might mitigate tacrolimus adverse effects. 7,9 Fifth, the authors speculate that NRM have a higher exposure to tacrolimus over time, leading to increased toxicity, which is not supported by data. In fact, others showed comparable area under the receiver operating characteristic curve between RM and NRM.…”
mentioning
confidence: 90%
“…for example, changes in gastrointestinal mobility, albumin, hematocrit, and steroid dosing, to allow valid prediction of the Tac metabolism type before one months after RTx [8,10].…”
Section: Transplant Internationalmentioning
confidence: 99%
“…
There is an emerging interest in the tacrolimus metabolism rate as it is linked to outcomes after transplantation [1][2][3][4][5][6][7]. We and others propose the concentration-to-dose (C/D) ratio as a simple surrogate for the individual tacrolimus (Tac) metabolism rate [5,8,9]. Recently, Jouve et al [3] showed in a large retrospective singlecenter study that the C/D ratio was in contrast to the CYP3A5 genotype strongly associated with outcomes after renal transplantation (RTx).
…”
mentioning
confidence: 99%
“…Tacrolimus (FK506) has become the rst-line immunosuppressant drug used after LT [11][12][13]. We determined the therapeutic e cacy of FK506 in an outbred rat LT model.…”
Section: Introductionmentioning
confidence: 99%